Existential Neuropsychology: A Science of Making Values - Asmolov, A; Falikman, M (KnE Life Sciences, 2018)
In neurorehabilitation and restoration of motor functions, there are Vygotsky–Luria’s line and Leontiev–Zaporozhets’ line that are obviously connected, but their connection isn’t articulated enough. Their point of convergence dates back to mid 1940s, but since then the development of the two lines was largely parallel. And the missing link is Nikolay Bernshtein’s non-classical biology of purposeful activity. Both lines are intrinsically based on his predictive explanatory framework, with the central role of task set in movement construction, which, in turn, determines the hierarchy of levels where backward reafference (‘sensory corrections’) takes place. Current neurorehabilitation disregards the Bernsteinian idea of the central role of values and meanings in the recovery of movements, which opposes neurorehabilitation as training, or instruction, to neurorehabilitation as guidance, the latter relevant to Leontiev’s ‘personal meaning’ problem. Neurorehabilitation as guidance is generation of the personal meaning, or ‘making values’, allowing to overcome bounds perceived as insuperable, the idea that brings it together with existential psychology and existential psychotherapy. Keywords: rehabilitation, task set, value, image of the desired future, physiology of activity, existential neuropsychology, personal meaning